Dietary vitamin a intake, coverage of vitamin a megadose supplementation, and prevalence of vitamin a deficiency among marginalized children 6-59 months in anganwadis of Chandigarh: A multistage cluster sampling survey - Rohit Yadav; Ajay Patial; Bhavneet Bharti; Savita Verma Attri; Prateek Bhatia (Wolters Kluwer Medknow Publications, 2021)
Background: Lack of recent local data regarding Vitamin A deficiency, dietary intake, and coverage of biannual high-dose Vitamin A prophylaxis among marginalized children poses challenges for policy change. Objective: Our study aimed to evaluate the burden of serum Vitamin A deficiency, dietary Vitamin A intake, and current Vitamin A supplementation coverage. Methodology: We enrolled 216 children aged 6-60 months from 30 Anganwadis of Chandigarh using two-stage cluster sampling. Results: Dietary intake of Vitamin A-rich foods and vegetables in the last 24 h was observed only in 20% of enrolled children. Although 79.21% (160/202) of children aged ≥9 months reported receiving Vitamin A supplementation, only 38.52% had documented record of age-appropriate complete supplementation. None of the children showed ocular manifestations of Vitamin A deficiency. For the subjects in which C-reactive protein levels were ≤5 mg/l (n = 148), 35.14% (52/148) had serum retinol ≤0.7 μmol/L and 2.03% (3/148) had serum retinol ≤0.3 μmol/L. The multivariate odds ratios (ORs) of Vitamin A deficiency (serum retinol <0.7) were 2.23 times higher in subjects with inappropriate complementary feeding (OR: 2.23; 95% confidence interval [CI]: 1.07-4.80; P = 0.035) whereas odds were significantly lower for middle (OR: 0.27; 95% CI: 0.09-0.76; P = 0.015) and higher income (OR: 0.14; 95% CI: 0.03-0.53; P = 0.005) families in reference to low-income group. Conclusions: Subclinical Vitamin A deficiency is still a public health crisis with suboptimal dietary intake of Vitamin A-rich foods and compromised food diversity necessitating targeted approach for marginalized children.